Georgia : First Review Under the Stand-by Arrangement and Request for Modification of a Performance Criterion-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Context. Macroeconomic developments have been in line with the program. Growth has recovered, led by domestic demand, with the Russia-Ukraine crisis having limited economic impact so far. Growth should reach 5 percent in 2014. Georgia and the EU started applying their Deep and Comprehensive Free Trade Area (DCFTA) agreement provisionally in September. Although some ministers left the cabinet in November, the ruling Georgian Dream government has kept its majority and has reaffirmed its commitment to Georgia's goal of increased European integration. Outlook and Risks. Growth should remain at 5 percent in 2015. Downside risks stem from possible escalation of regional tensions and weaker recovery in the Euro area. On the upside, lower oil prices could boost growth and reduce the current account deficit. Policies. Although this year's fiscal deficit should come in below target, the composition of spending has again shifted from capital to current and the substantial increase in government spending planned for the fourth quarter could lead to balance of payments pressures. The 3 percent of GDP deficit in the 2015 draft budget is consistent with the program objectives of preserving fiscal sustainability and supporting external adjustment. The draft budget envisages increases in pensions, teacher salaries, drug benefit coverage, and capital spending paid for by higher excises on tobacco, alcohol, and incoming international phone calls. Annual inflation rose to 3 1\2 percent in October but remains below the National Bank of Georgia's (NBG) inflation target of 6 percent for 2014. The stability of the lari against the U.S. dollar has resulted in appreciation against key trading partners. The current account deficit has widened in 2014 as expected with the economic recovery but should decline in the medium term supported by fiscal consolidation, exchange rate flexibility, reforms to improve competitiveness, and greater trade opportunities. Reserve accumulation under the program will strengthen resilience to shocks. The NBG is committed to implementing the FSAP recommendations. Program. The program is on track, with all September conditionality met except for the structural benchmark on preparing an access to finance study which has now been reset. SDR40 million will become available upon the completion of the review.